The Relationship between Entrepreneurial Characteristics and Business Performance of SMEs Producing Keripik Balado in Bukittinggi City - Ananda, Pinta Aftaprilia Rizki; Amir, Reza Mardhiyah (ITScience (Information Technology and Science), 2025)
Small and medium enterprises (SMEs) are crucial in supporting regional economic growth, particularly in Bukittinggi City, which is widely recognized as a prominent tourist destination and a center for traditional West Sumatran snacks. Among the leading products produced in the region is keripik balado (spicy cassava chips), which has become an iconic commodity with high market demand. This study examines the entrepreneurial characteristics of keripik balado SME owners and their relationship with business performance. A mixed-method research design was adopted, employing purposive sampling to select 35 respondents from the city’s main sales center. Data were analyzed using the Spearman correlation with SPSS and Microsoft Excel. The results reveal that specific entrepreneurial traits—namely hard work, innovativeness, and leadership—are significantly associated with business performance indicators, including sales volume, market expansion, and profitability. Conversely, self-confidence and independence did not demonstrate a statistically significant relationship with performance outcomes. These findings suggest that while multiple characteristics contribute to entrepreneurial success, certain traits exert a stronger influence. Therefore, strengthening these key attributes could be an effective strategy in SME development programs, particularly within the food industry sector in Bukittinggi and similar regional contexts.